Financial structure and economic growth a cross-country comparison of banks, markets, and development - Demirguc-Kunt Asli; Levine Ross (Cambridge MIT Press, 2001)
The book contains recently acquired cross-country data from almost 150 countries. It includes information on the size, efficiency, and activity of banks, insurance companies, pension and mutual funds, finance companies, and stock and bond markets. It als
Accompanies a CD-ROM bearing acc no D607
Keywords: Banks and banking; Case studies; Economic development; Financial institutions; Stock exchanges